2021
DOI: 10.1080/20464177.2021.1949088
|View full text |Cite
|
Sign up to set email alerts
|

iWindCrfield trial and electrochemical analysis for corrosion detection and monitoring offshore wind turbine’s MP-TP steel components

Abstract: A Proof-of-Concept (POC) low power-low current wireless sensor network (WSN) for corrosion detection and monitoring of offshore wind turbine (OWT)'s component, entitled iWindCr, has been developed and field trialled in one of the OWTs in the UK south region. This paper reports on the setting up and outcomes of this field trial. The trial has successfully demonstrated the working functionality of the WSN by measuring changes of the Open Circuit Potential (OCP) and Zero Resistance Ammeter (ZRA) electrochemical p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Recent studies on full-scale ship and offshore structure corrosion monitoring have revealed notable methodologies. Simandjuntak et al (2021) applied electrochemical sensors in their monitoring application for offshore wind turbines in the United Kingdom. Their research delves into the reliability of electrochemical sensors in estimating corrosion rates in offshore environments.…”
Section: Module 1–1: On-site Measurements Of In-service Damagementioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies on full-scale ship and offshore structure corrosion monitoring have revealed notable methodologies. Simandjuntak et al (2021) applied electrochemical sensors in their monitoring application for offshore wind turbines in the United Kingdom. Their research delves into the reliability of electrochemical sensors in estimating corrosion rates in offshore environments.…”
Section: Module 1–1: On-site Measurements Of In-service Damagementioning
confidence: 99%
“…Despite recent advancements in individual technologies, certain ones may still be in their early stages of development or impractical for implementation within a real ship and offshore structure’s DHE system. Hence, we propose a prototype system that leverages practical technologies and approaches to ensure the lifetime healthcare of aging ships and offshore structures.
Figure 3. Photographs of a field trial for in situ monitoring on the existing offshore structures: (a) electrochemical sensor (Simandjuntak et al, 2021); (b) optical fiber strain sensor (Lee and Chung, 2016); (c) image processing technology (Momber, 2016); and (d) Visual inspection (DEEPWATER, 2022).
…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation